Blood storage affects the detection of cellular prion protein on peripheral blood leukocytes and circulating dendritic cells in part by promoting platelet satellitism - Glier, Hana; Holada, Karel (Journal of immunological methods, 2012)
BACKGROUND: Flow cytometry represents an attractive approach for developing currently unavailable screening tests for prion diseases. Several studies have reported significant differences in the binding of antibodies directed against cellular prion protein (PrP(C)) to blood cells of prion-infected subjects compared with healthy controls. However, flow cytometry data usually show large individual variations in detected PrP(C) levels in both infected and control groups, rendering the interpretation of individual patient data difficult. OBJECTIVES: To determine how pre-analytical variables, such as the choice of anticoagulant, whether or not the blood was stored, and the storage temperature, affect the detection of PrP(C) in blood cells. METHODS: Blood from healthy donors was collected in EDTA or citrate anticoagulant and processed either immediately or after storage overnight at room temperature or at 4°C. The expression of PrP(C) by T cells, B cells, NK cells, monocytes and circulating dendritic cells was evaluated using quantitative flow cytometry with the PrP(C) monoclonal antibodies AG4 and AH6. RESULTS: The anticoagulation of blood with citrate resulted in decreased levels of PrP(C) on monocytes but not the other cell types. The storage of blood prior to analysis led to a significant decrease in the levels of PrP(C) on the cells studied, although there were substantial differences between the cell populations. This decrease was more pronounced when using mAb AG4, which targets the N-terminal portion of the PrP(C) molecule, or following storage at room temperature. Moreover, we identified platelet satellitism on leukocytes, especially on monocytes and granulocytes, as an additional factor contributing to the heterogeneity of PrP(C) detection in stored blood. CONCLUSIONS: Our study demonstrates that the storage of blood prior to analysis greatly affects the detection of PrP(C) by flow cytometry. To limit the inclusion of storage-generated artifacts, we recommend the processing of blood samples immediately after their collection.
Keywords: Citric Acid; dospělí; antikoagulancia; Edetic Acid; průtoková cytometrie; Adult; Blood Specimen Collection; Dendritic Cells; Anticoagulants; trombocyty; dendritické buňky; lidé; EDTA; Flow Cytometry; kyselina citronová; Blood Platelets; leukocyty; Prions; odběr vzorku krve; Leukocytes; lidé středního věku; priony; Middle Aged; Humans